2014
DOI: 10.4172/2167-0846.s3-003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Identification Of Spinal Cord-Infiltrating CD4+ T Lymphocytes In A Murine Model Of Neuropathic Pain

Abstract: BackgroundNeuropathic pain is one of the most devastating kinds of chronic pain. Neuroinflammation has been shown to contribute to the development of neuropathic pain. We have previously demonstrated that lumbar spinal cord-infiltrating CD4+ T lymphocytes contribute to the maintenance of mechanical hypersensitivity in spinal nerve L5 transection (L5Tx), a murine model of neuropathic pain. Here, we further examined the phenotype of the CD4+ T lymphocytes involved in the maintenance of neuropathic pain-like beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Animal studies have enlightened the role of T cells in pain development. In particular, the depletion of CD4 + T cells in a mouse model was able to inhibit thermal hyperalgesia and tactile central sensitization following partial sciatic nerve ligation [57,58].…”
Section: Role Of T Cells In Fibromyalgia: Literature Datamentioning
confidence: 99%
“…Animal studies have enlightened the role of T cells in pain development. In particular, the depletion of CD4 + T cells in a mouse model was able to inhibit thermal hyperalgesia and tactile central sensitization following partial sciatic nerve ligation [57,58].…”
Section: Role Of T Cells In Fibromyalgia: Literature Datamentioning
confidence: 99%
“…In addition to macrophages, T cells may also be important in the mechanisms that underlie pathological pain. For instance, activated CD4 + T cells, specifically Th1 and Th17 cells, migrate to associated lumbar DRG and/or the lumbar spinal cord dorsal horn in animal models of sciatic nerve transection (47)(48)(49), spared nerve injury (50,51), partial sciatic nerve ligation (52,53), and sciatic nerve chronic constriction injury (54).…”
Section: T Cells In Pathological Painmentioning
confidence: 99%
“…They found that neuropathic pain is mediated by Th1 cells. 73 A recent experiment demonstrated that T cells infiltrate the dorsal root ganglion following peripheral nerve injury. Once in the dorsal root ganglion, they release leukocyte elastase, a proteinase that destroys bacteria and which has been linked to chronic inflammation.…”
Section: Immune Cell Involvement In Painmentioning
confidence: 99%